Draft Special Component Plan 1990-95 and 1991-92 Union Territory of Pondicherry - Planning Commission (Planning Commission, 1990)
The Union Territory of Pondicherry Consists of four regions, namely Pondicherry, Karaikal, Mahe and Yanam lying geographically isolated from one another. Pondicherry region which is on the east coast about 162 kms. South of Madras is the largest of these and consists of 12 scattered areas interspersed with enclaves of South Arcot District of Tamil Nadu. Karaikal region is about 150 kms.
Government of Pondicherry, Planning and Research Department